Application of Automated Complex Gas Reaction Controller for Hydrogen Storage Materials Investigation; Advanced Materials Research; Vol. 740 : Advanced Materials Research - Kudiyarov V. N. Victor Nikolaevich; Gulidova L. V. Ludmila Vladimirovna; Lider A. M. Andrey Markovich; Pushilina N. S. Natalia Sergeevna (Materials Properties, Measuring Methods and Applications, 2013)
Title screen